STUDI KELENGKAPAN PENJELASAN INFORMASI CARA PENGGUNAAN CONTROLLERMETERED-DOSE INHALER (MDI) YANG MENGANDUNG KORTIKOSTEROID SEBAGAI TERAPI ASMA DI APOTEK KABUPATEN TUBAN - Amelia Lorensia; Jessica Nathania (Jurnal Ilmiah Manuntung, 2017)
This experiment centred in metered dose inhaler (MDI) device which used routinely by asthma patient as controller therapy. MDI used ask patient’s skill more when using their medication. MDI technique informnation provided by pharmachist are important to achive optimal medication in asthma therapy. By a non experimental study, mysterious patient collect MDI technique gived by pharmacist in Tuban pharmacy using observacional and cross sectional method. Information about MDI technique comprehensive collected by two ratter as mysterious patient which assessed with checklist that got measseured by kappa to know ratter aggrement percentage. The result showed from a total sampling under 41 pharmachist which represent each 41 pharmacy in Tuban, by purposive sampling Pharmacists as pharmaceutical personnel responsible for information services at pharmacies, including information on how to use MDI. Most of the apothecary's ability level in providing information is still lacking, then continued with adequate technique, and optimal technique in providing complete information of MDI use for asthma patient. Pharmacists know how to use MDI and no pharmacist is unexpected or not familiar with MDI as an asthma therapy. Pharmacists in Tuban district have a tendency to inform only four stages of the nine stages of MDI use from Osman et al (2012), ie at the 1st, 3rd, 5th, and 6th stages of MDI use